Organic agriculture in Africa: a critical review from a multidisciplinary perspective - Abele, S.; Dubois, T.; Twine, Edgar E.; Sonder, K.; Coulibaly, O. (2007)
Organic agriculture seems to be a profitable enterprise for small scale farmers in developing countries, also in Africa, to enter high value markets in the Northern hemisphere and overcome the crises of declining terms of trade on global agricultural produce markets. It is also seen as a way to overcome food security problems, induced by low yields and declining productivity of African smallholder agriculture. This paper discusses the present situation on European organic markets and their potential for small scale farmers in Africa, finding that although markets in the North are still growing, they might be limited in the long run. Barriers to entry are many, including the lack of affordable certification bodies in Africa, poor infrastructure and experience in organic production and marketing, as well as regulation in European markets, and increasing risks and competition associated with the process of market saturation. Organic agriculture has not yet proven to solve the problems of food security and declining terms of trade in Africa. It is also clear that there is a lot of inequity in the organic chains, and that so far only the relatively large scale farmers in Africa, as well as middlemen and traders along the chain, profit from commercial organic agriculture, similar to findings from conventional commercial agriculture. Organic agriculture is being researched by international agricultural research organizations, and it is found to be less yielding and more risky than integrated approaches that combine organic and synthetic inputs. This research has to be still extended, and research gaps, especially in terms of costs and benefits, have to be closed to get a final picture on how to integrate and optimise the various approaches.